ASCENT: A Provably Terminating Decentralized Logging Service. (7th September 2017) - Bonnaire, Xavier; Cortés, Rudyar; Kordon, Fabrice; Marin, Olivier
Abstract: Building a certification authority that is both decentralized and fully reliable is impossible. However, the limitation thus imposed on scalability is unacceptable for many types of information systems, such as e-government services, which require an infrastructure able to support heavy computation loads while remaining highly reliable. Our scalable approach opts for the next best thing to full reliability: a certification authority with a probability of arbitrary failure so low that, in practice, false positives should never occur.